2018
DOI: 10.1021/acsphotonics.8b01033
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Optical Gain in CdSe/CdS Dots-in-Rods

Abstract: Excitonic-state-resolved pump/probe spectroscopy is performed on semiconductor dot-in-rod nanocrystals. Using excitonic-state-resolved pumping we are able to resolve effects of the rod upon exciton dynamics of the core. The shell has the effect of lowering gain threshold, increasing absorption cross-section, and increasing the Auger lifetime; hence nanorods are shown to be an effective means of enhancing gain performance of nanomaterials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 64 publications
1
21
0
Order By: Relevance
“…Colloidal semiconductor nanocrystals (NCs) have been considered as an excellent material platform for light amplification applications thanks to their solution processability, low‐cost production, and wide spectral tunability achieved by altering their shape, size, and composition . Various shapes of the semiconductor NCs including colloidal quantum dots (CQDs), nanorods (NRs), colloidal quantum wells, and perovskite nanocrystals have been utilized as potent gain media for the optical gain and lasing applications.…”
Section: Introductionmentioning
confidence: 99%
“…Colloidal semiconductor nanocrystals (NCs) have been considered as an excellent material platform for light amplification applications thanks to their solution processability, low‐cost production, and wide spectral tunability achieved by altering their shape, size, and composition . Various shapes of the semiconductor NCs including colloidal quantum dots (CQDs), nanorods (NRs), colloidal quantum wells, and perovskite nanocrystals have been utilized as potent gain media for the optical gain and lasing applications.…”
Section: Introductionmentioning
confidence: 99%
“…These fluorescence properties are advantageous for a wide range of applications, for example, as fluorescent reporters/markers , or, in combination with the possibility for solution-processing, as building units in display devices. , The growth of an enclosing shell further improves the photostability and fluorescence quantum yield (QY). , When a spherical core is surrounded by an elongated rod-shaped shell, that is, for the so-called dot/rod nanoparticles (DRs), additional optical properties evolve. For example, it has been shown that the broken spherical symmetry leads to linear polarization of both absorption and emission, , as well as the possibility to efficiently separate the charge carriers along the DR axis. , In addition, the high absorption cross section of the shell material results in an increase of the molar extinction coefficients and also of the optical gain. In particular, the possibility to switch the fluorescence, via polarizing optical components or external electric fields, combined with various methods for the fabrication of large-scale ordered assemblies of DRs is highly relevant for the realization of nanoparticle devices in display technology and solid-state lighting.…”
Section: Introductionmentioning
confidence: 99%
“…[27] Copyright 2015, American Chemical Society. relationship, even though their higher absorption cross-section and lower Auger recombination rates (≈10 10 s −1 vs ≈10 11 s −1 for QDs) [282] would make them interesting materials for lasing.…”
Section: Ordered Semiconductor Nanoparticle Films As Optical Gain Med...mentioning
confidence: 99%
“…Similarly, nanorod assemblies have not been investigated in depth concerning their superstructure–optical gain relationship, even though their higher absorption cross‐section and lower Auger recombination rates (≈10 10 s −1 vs ≈10 11 s −1 for QDs) [ 282 ] would make them interesting materials for lasing. The few examples of lasing in nanorod assemblies mostly relied on drop‐casting, upon which nanorods accumulate at the “coffee ring,” i.e., the outer edge of the drop‐casted area.…”
Section: Properties and Applicationmentioning
confidence: 99%